The Culture of the Highland Valley of Mexico II. Ethnological and Ethnobotanical Studies in Some Municipalities of Puebla, Mexico - Maiti, Ratikanta (International Journal of Bio-resource and Stress Management, 2010)
The paper presents an exploratory study of ethnoecology and ethnobotany in some municipalities around the great and dangerous volcano, Popocatepetl, Puebla. It discusses the vagaries of climate, social-culture and diversity of biotic resources on which the native communities with diverse ethnic culture are highly dependent for their livelihood. To our knowledge no such studies have been undertaken to understand their ethnic problems, cultures and biodiversity of these localities around the volcano. Concerted research activities need to be directed to understand ethnic culture, social problems and biodiversity of these important, but neglected communities of these regions that succumbed to volcanic disaster of volcano Popo. There is great necessity to preserve the ethnic culture of these neglected communities `